Modified Natural Rubber Based on the Sulphur Curing System as Rubber Compound Formulation on Basic Design of Seismic Bearing - Cifriadi, Adi; Sugita, Purwantiningsih; Kemala, Tetty; Nikmatin, Siti; Puspitasari, Santi; Falaah, Asron Ferdian; Wijaya, Usman (Syarif Hidayatullah State Islamic University, 2024)
Indonesia is highly susceptible to earthquakes, with the southern and western coasts of Java and Sumatra being the most vulnerable regions. Due to this vulnerability, it is necessary to establish a culture of disaster mitigation in the most fertile and heavily populated islands to reduce the number of fatalities and economic losses caused by earthquakes. One of the promising real-world seismic base isolation methods is using a rubber seismic bearing constructed of rubber and metal layers. This study aimed to examine the typical behavior of natural rubber compounds subjected to various sulfur-curing processes as basic designs in the manufacture of rubber seismic bearings. The experiment was carried out by arranging the sulfur curing system into three categories, namely an efficient which applied N-cyclohexyl-2-benzothiazole sulfonamide (CBS)/Sulfur (S) ratio as 1.4/0.15 and 1.4/0.25, semi-efficient with CBS/S ratio of 1.4/1.4 and 1.4/1.7, and conventional with CBS/S ratio of 1.4/3.0 and 1.4/3.5. The results showed that the ideal modification condition for NR macromolecule chain found in seismic-bearing rubber compound was a semi-efficient sulfur curing system with a CBS/S ratio of 1.4/1.4. It suggested that a semi-efficient sulfur curing system was appropriate for developing rubber compound formulation for seismic rubber bearings, mainly for low-damping types.